Temperature-induced variation in sexual maturation of Japanese anchovy Engraulis japonicus. (10th April 2015) - Yoneda, Michio; Yamamoto, Masayuki; Yamada, Tetsuo; Takahashi, Makoto; Shima, Yasuhiro
Abstract : Temperature is one of the most influential factors for the sexual maturation of fishes, but understanding of the extent to which temperature affects the maturational schedules is limited in multiple-spawning fishes over a protracted season. This study examined the effect of temperature on sexual maturation of Japanese anchovy Engraulis japonicus siblings under high and low temperature regimes on different birthdates. The maturation probability differed between the two temperature regimes. Specimens in high temperature regimes matured at much smaller size and younger age than their counterparts. Also, a significant difference in the maturation probability between sexes was found at low temperatures, but not at high temperatures. Our findings show that temperature affects the maturational schedules of siblings of Japanese anchovy, suggesting that the size and age at sexual maturation could differ among cohorts, even in a given sampling location and/or year.